Minimally invasive video-assisted cervical ventral slot in dogs - Leperlier, D.; Manassero, M.; Blot, S.; Thibaud, J. L.; Viateau, V. (Veterinary and Comparative Orthopaedics and Traumatology, 2011)
Objectives: To investigate the feasibility of a minimally invasive video-assisted (MIVA) cervical ventral slot (VS) in dogs without the use of fluoroscopy, and to report our initial clinical experiences in dogs.Methods: Two surgical approaches to an inter-vertebral disk space (IVDS) were performed in eight intact canine cadavers to determine the feasibility of MIVA-VS using the Destandau Endospine™ Devicea (DED) without fluoroscopic guidance. In a subsequent clinical study, 10 client-owned dogs admitted for a Hansen type 1 disk extrusion underwent a MIVA-VS. Recorded data in both studies included: incision lengths, correct targeting of the IVDS, technical problems encountered during the procedure, and potential damage to major anatomical structures. In the 10 clinical cases, duration of the procedure and clinical outcome at five and 12 days, and after a minimum of three months were also recorded.Results: Correct exposure of the targeted IVDS was achieved in all cases. There was no major iatrogenic damage. Mean skin incision length was 39 mm and mean surgery time was 52 minutes. The technique provided increased illumination and magnification of the surgical field. Recovery was uneventful in all cases.Clincial relevance: The present study provided evidence that MIVA-VS using the DED was feasible and a relatively fast and safe procedure for the treatment of cervical disk herniation. Advantages of the technique seemed to include shorter incisions, less dissection and improved visibility.
Keywords: Ventral slot; video-assisted; dogs; disk; hernia